S-18-4: ACE2 IS INVOLVED IN SARS-COV-2 INDUCED ENDOTHELIAL CELL INFLAMMATION INDEPENDENT OF VIRAL REPLICATION. (January 2023) - Montezano, Augusto; Camargo, Livia L; Mary, Sheon; Neves, Karla B; Rios, Francisco J; Lopes, Rheure A; Beattie, Wendy; Herbert, Imogen; Herder, Vanessa; Szemiel, Agnieszka M; McFarlane, Steven; Palmarini, Massimo; et al.
Abstract : Objective: COVID-19 association with cardiovascular disease is thought to be due to endothelial cell inflammation. ACE2 interactions with SARS-CoV-2 spike protein S1 subunit is important to viral infection. Here we questioned whether SARS-CoV-2 induces vascular inflammation via ACE2 and whether this is related to viral infection. Design and Methods: Human microvascular endothelial cells (EC) were exposed to recombinant S1p (rS1p) 0.66 ug/mL for 10 min, 5 h and 24 h. Gene expression was assessed by RT-PCR and levels of IL6 and MCP1, as well as ACE2 activity, were assessed by ELISA. Expression of ICAM1 and PAI1 was assessed by immunoblotting. ACE2 activity was blocked by MLN4760 (ACE2 inhibitor) and siRNA. Viral infection was assessed by exposing Vero E6 (kidney epithelial cells; pos ctl) and EC to 105 pfu of SARS-CoV-2 where virus titre was measured by plaque assay. Results: rS1p increased IL6 mRNA (14.2 ± 2.1 vs. C:0.61 ± 0.03 2^-ddCT) and levels (1221.2 ± 18.3 vs. C:22.77 ± 3.2 pg/mL); MCP1 mRNA (5.55 ± 0.62 vs. C:0.65 ± 0.04 2^-ddCT) and levels (1110 ± 13.33 vs. C:876.9 ± 33.4 pg/mL); ICAM1 (17.7 ± 3.1 vs. C:3.9 ± 0.4 AU) and PAI1 (5.6 ± 0.7 vs. C: 2.9 ± 0.2), p < 0.05. MLN4760, but not rS1p, decreased ACE2 activity (367.4 ± 18 vs. C: 1011 ± 268 RFU, p < 0.05) and blocked rS1p effects on ICAM1 and PAI1. ACE2 siRNA blocked rS1p-induced IL6 release, ICAM1, and PAI1 responses as well as rS1p-induced NFkB activation. EC were not susceptible to SARS-CoV-2 infection, while the virus replicated well in Vero E6. Conclusion: rS1p induces an inflammatory response through ACE2 in endothelial cells; an effect that was independent of viral infection.